The situation and role of higher education in the North Hungary region - Lőrincz, Mónika (Acta Agraria Debreceniensis, 2015)
Northern Hungary is one of the most disadvantageous regions of Hungary and the European Union; "keeping force" is extremely week. The regional spatial inequalities – despite the national and EU convergence program – have been increasing year by year. The social and economic situation of the region shows negative trends. Negative features of the migration processes are manifested in the candidates’ choice for tertiary education has increased in the region in the past three years parallel with the proportion of those who are not on site, but primarily in the Central Hungarian region to continue their studies. An intensification of the negative trends is experienced in the economic processes both in jobs and the structure and performance of the local economy in respect of per capita income. The transition from the nineties has decisively influenced the social and economic processes and the status of tertiary education institutions and their constantly changing role in the region. The role of education has become a key point of their activities as financing of the sector encouraged the institutions to increase the number of students and training offer, while R&D as form of cooperation in the economic sphere overshaded. Nowadays and over the past decade the increasing demand to transform their educational profile has increased in accordance with the social and economic situation of the region, adjusted to the catch-up and development opportunities of the region.